2003
DOI: 10.1007/s00404-002-0296-5
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic implications of anaemia in the outcome of patients with early stages of uterine cervix carcinoma

Abstract: We studied the prognostic value of anaemia in the evolution of patients with early stages of uterine cervix cancer and treated with radical surgery. An observational study of 114 patients treated for cervical cancer at the "La Fe" Maternity Hospital in Valencia (Spain) during the period 1971 to 1989. Survival analyses were carried out whereby both recurrence and mortality rates were considered. The level of haemoglobin influences the prognosis of the patients in the study presented, and explains a variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…29 However, receipt of perioperative RBC transfusion in the setting of radical hysterectomy for early-stage cervical cancer does not seem to impact recurrence or OS. 30,31 In addition, although erythropoietin seems to increase the risk for thromboembolic events in cervical cancer, 32 its use does not seem to be detrimental to DFS or OS in either cervical 33,34 or ovarian cancer 35 survival.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, receipt of perioperative RBC transfusion in the setting of radical hysterectomy for early-stage cervical cancer does not seem to impact recurrence or OS. 30,31 In addition, although erythropoietin seems to increase the risk for thromboembolic events in cervical cancer, 32 its use does not seem to be detrimental to DFS or OS in either cervical 33,34 or ovarian cancer 35 survival.…”
Section: Discussionmentioning
confidence: 99%
“…12 Results from recent studies in patients undergoing surgery for head and neck cancer, cervical cancer, uterine cancer, and non-small-cell lung cancer supported this conclusion by demonstrating that anemia is an independent prognostic factor for decreased locoregional control, disease-free survival, and overall survival. [13][14][15][16][17][18] Reviews of the available evidence have demonstrated a strong relationship between anemia and decreased quality of life in patients with cancer, 19,20 but clinical studies of this association typically have focused on chemotherapy-associated anemia, not anemia in patients with cancer who underwent surgery. Additional study would be needed to determine whether the association between anemia and postoperative morbidity, mortality, and quality of life exists in patients who are undergoing cancer-related surgery.…”
Section: Consequences Of Anemiamentioning
confidence: 99%
“…According to Obermair et al [15], only patients with hemoglobin values [11 g/dl throughout chemoradiation had more than 90% chance of achieving a complete clinical response. Also Martin-Loeches et al [16] indicated that patients with hemoglobin levels of less than 13 g/dl had a less favorable prognosis. Furthermore, they pointed out that hemoglobin levels are equally important in its influence on prognosis and patient evolution as the volume of the tumor itself.…”
Section: Discussionmentioning
confidence: 97%